New frontiers review of some recent conservation techniques of organic and inorganic archaeological artefacts against microbial deterioration - Geweely, Neveen S. (Frontiers in Microbiology, 2023)
The information on the advances and technology of some recent conservation methods (2020-2023) of organic and inorganic archaeological objects against microbial deterioration is recorded. An outline of comparative new protective methods for conserving plant-origin organic artefacts {Fibers (manuscripts, textile) and wood}, animal-origin organic artefacts (painting, parchment and mummies) and inorganic stone artefacts were investigated. The work not only contributes to the development of safe revolutionary ways for more efficient safe conservation of items of historical and cultural worth but also serves as a significant diagnostic signature for detecting the sorts of microbial identification and incidents in antiques. Biological technologies (environmentally friendly green biocides) are the most used recent, efficient and safe strategy acceptable as alternatives to stop microbial deterioration and prevent any potential interactions between the biological agent and the artefacts. Also, a synergistic effect of combining natural biocides with mechanical cleaning or chemical treatments was suggested. The recommended exploration techniques should be considered for future applications.